Acquired cystic disease-associated renal cell carcinoma with PTCH1 mutation: a case report - Zhou, Luting; Xu, Haimin; Liu, Yang; Li, Xiangyun; Li, Chuanying; Yang, Xiaoqun; Wang, Chaofu (Frontiers in Oncology, 2024)
Acquired cystic disease-associated renal cell carcinoma (ACD-RCC) is an extremely rare kidney tumor seen mainly in patients with end-stage renal disease. Currently, there are few reports on this type of tumor. We describe the case of a 58-year-old man who had been receiving peritoneal dialysis for more than nine years due to chronic renal insufficiency and uremia. One year after undergoing left renal clear cell renal cell carcinoma resection, a space-occupying lesion was found in the right kidney for which he underwent right nephrectomy. The histopathology of this tumor showed solid or tubular cell arrangements, with some areas of cyst formation. Vacuoles of varying sizes were present in the cytoplasm, and varying amounts of calcium oxalate crystals were found in the tumor cells or interstitium. The pathological diagnosis was ACD-RCC. Next-generation sequencing detected mutations in the PTCH1, MTOR, FAT1, SOS1, RECQL4, and CDC73 genes in the right renal tumor. This is a rare case of a patient with ACD-RCC in the right kidney and clear cell renal cell carcinoma in the left kidney. The findings suggest that mutations in PTCH1 associated with ACD-RCC may have acted as oncogenic drivers for the development of ACKD-RCC, together with providing insight into mechanisms underlying ACD-RCC development, as well as diagnostic and treatment options.